Media Internal Berbasis Aplikasi PJB M-Office dan Kinerja Karyawan - Totok Wahyu Abadi; Fauji Bagus Permadi (Universitas Muhammadiyah Sidoarjo, 2018)
None of the world-class corporations did not use communication information technology (ICT) in running their business wheels. ICT had become a social engineering technology for the advancement of a corporation. The purpose of this study discussed effect of use of internal media based on PJB mOffice, information accessibility, and corporate communication climate on employee performance. By using organizational communication theory, technology acceptance model (TAM) measured usefulness of PJB mOffice applications, information accessibility, corporate communication climate and employee performance. This study located at Pembangkitan Jawa-Bali Head Office in Surabaya with a sample of 82 permanent employees who installed and used the PJB mOffice application as respondents. Data was collected by questionnaires randomly. Analyzing data used multiple linear regression with SPSS 20. The results showed that the use of android-based internal relations media, information accessibility, and organizational communication climate simultaneously had an effect on employee performance. The most influential factor in employee performance was corporate communication climate. The better and conducive to the corporate communication climate, the higher the employee's performance. The use of android-based media internal relations and corporate information accessibility was not a determinant in improving employee performance.